Act of Mar. 15, 1927, ch. 261, § 79, Idaho Gen. Laws 510, 541 - (:unkn) unknown (General Publisher, 1927)
Prohibited any body of men to organize as a militia or parade in public with firearms in any city or town unless recognized by the laws of Idaho and United States. Prohibited any city ot town from arming, equipping, uniforming, supporting, sustaining, providing armories, or providing space to drill to any such body of men.
--
Keywords: MILITIAS